Image Cloud Recognition Based on Public History as a Learning Media to Improve Historical Thinking of Non-Formal Education Students - Amin, Syaiful; Shofwan, Imam; Rashid, Salman (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2026)
Amid the increasing influence of global economic, technological, and cultural transformations, history education faces challenges in maintaining its relevance and meaningfulness for students. Although previous studies have emphasized the importance of contextual and technology-supported history learning, limited attention has been paid to integrating cloud-based image recognition technology with local public history content, particularly in secondary education in Indonesia. This study aims to develop and examine the effectiveness of public history–based Image Cloud Recognition (ICR) media in improving students’ historical thinking skills. The research employed a research and development approach using the ADDIE model, combined with a quasi-experimental pretest–posttest design. The participants comprised 2 history teachers and 60 high school students in Semarang City, who were divided into experimental and control groups. Data were collected through questionnaires, interviews, and historical thinking tests and analyzed using an independent-samples t-test. The findings indicate that the use of ICR media significantly improves students’ historical thinking skills compared to conventional learning, as evidenced by t-values of 8.778 and 10.239, which exceed the critical value (1.672) at p < 0.05. These results suggest that ICR media is effective in facilitating contextual, visually rich, and meaningful history learning, thereby enhancing students’ critical engagement with historical events.